Systemic Parathyroid Hormone Enhances Fracture Healing in Multiple Murine Models of Type 2 Diabetes Mellitus. (2nd April 2020) - Alder, Kareme D; White, Andrew HA; Chung, Yeon‐Ho; Lee, Inkyu; Back, JungHo; Kwon, Hyuk‐Kwon; Cahill, Sean V; Hao, Zichen; Li, Lu; Chen, Fancheng; Lee, Saelim; Riedel, Matthew D; et al.
ABSTRACT: Type 2 diabetes mellitus (T2DM) is a multisystemic disease that afflicts more than 415 million people globally—the incidence and prevalence of T2DM continues to rise. It is well‐known that T2DM has detrimental effects on bone quality that increase skeletal fragility, which predisposes subjects to an increased risk of fracture and fracture healing that results in non‐ or malunion. Diabetics have been found to have perturbations in metabolism, hormone production, and calcium homeostasis—particularly PTH expression—that contribute to the increased risk of fracture and decreased fracture healing. Given the perturbations in PTH expression and the establishment of hPTH (1–34) for use in age‐related osteoporosis, it was determined logical to attempt to ameliorate the bone phenotype found in T2DM using hPTH (1–34). Therefore, the present study had two aims: (i) to establish a suitable murine model of the skeletal fragility present in T2DM because no current consensus model exists; and (ii) to determine the effects of hPTH (1–34) on bone fractures in T2DM. The results of the present study suggest that the polygenic mouse of T2DM, TALLYHO/JngJ, most accurately recapitulates the diabetic osteoporotic phenotype seen in humans and that the intermittent systemic administration of hPTH (1–34) increases fracture healing in T2DM murine models by increasing the proliferation of mesenchymal stem cells. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.